Teacher Development Training Programmes and Junior Secondary School Goal Attainment in Rivers State - Okai N. Okai; Mike-Tamunotonye Uloma (Research Parks Publishers, 2022)
This study examined teacher development training programmes and junior secondary school goal attainment in Rivers State. three research questions and three corresponding null hypotheses guided the study. The sample for this study was 702 teachers, constituting 20% of the original population which was 3,510 teachers. In this regard, 586 teachers were drawn from the urban schools and 116 from the rural schools brining the universe of the sample for this study to 702. A stratified random sampling technique was used in selecting the schools while the simple random sampling technique was used in selecting the teachers. A self-structured questionnaire titled: Teacher Development Training Questionnaire (TDTQ) was used to elicit data. The test-retest was computed using Pearson Product Moment Correlation Coefficient and a result of 0.71 alpha was obtained. The weighted mean and standard deviation were used to answer the research question while the z-test was used to test the hypotheses at 0.05 level of confidence.